Human Mesenchymal Stem Cell‐Derived Miniature Joint System for Disease Modeling and Drug Testing - Zhong Li; Zixuan Lin; Silvia Liu; Haruyo Yagi; Xiurui Zhang; Lauren Yocum; Monica Romero‐Lopez; Claire Rhee; Meagan J. Makarcyzk; Ilhan Yu; Eileen N. Li; Madalyn R. Fritch; et al. (Advanced Science, 2022)
Abstract Diseases of the knee joint such as osteoarthritis (OA) affect all joint elements. An in vitro human cell‐derived microphysiological system capable of simulating intraarticular tissue crosstalk is desirable for studying etiologies/pathogenesis of joint diseases and testing potential therapeutics. Herein, a human mesenchymal stem cell‐derived miniature joint system (miniJoint) is generated, in which engineered osteochondral complex, synovial‐like fibrous tissue, and adipose tissue are integrated into a microfluidics‐enabled bioreactor. This novel design facilitates different tissues communicating while still maintaining their respective phenotypes. The miniJoint exhibits physiologically relevant changes when exposed to interleukin‐1β mediated inflammation, which are similar to observations in joint diseases in humans. The potential of the miniJoint in predicting in vivo efficacy of drug treatment is confirmed by testing the “therapeutic effect” of the nonsteroidal anti‐inflammatory drug, naproxen, as well as four other potential disease‐modifying OA drugs. The data demonstrate that the miniJoint recapitulates complex tissue interactions, thus providing a robust organ chip model for the study of joint pathology and the development of novel therapeutic interventions.